2000
DOI: 10.1111/j.1748-7692.2000.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

FORAGING STRATEGIES OF SYMPATRIC KILLER WHALE (ORCINUS ORCA) POPULATIONS IN PRINCE WILLIAM SOUND, ALASKA

Abstract: Killer whales (Orcinus orca) feed on a wide variety of fish, cephalopods, and marine mammals throughout their cosmopolitan range; however, the dietary breadth that characterizes the species is not reflected in all populations. Here, we present the findings of a 14‐yr study of the diet and feeding habits of killer whales in Prince William Sound, Alaska. Two non‐associating forms of killer whale, termed resident and transient (Bigg et al. 1987), were identified. All prey seen taken by transients were marine mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
222
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(233 citation statements)
references
References 24 publications
10
222
1
Order By: Relevance
“…Lower d 15 N values at the base of the food chain in the Central Aleutian islands (Kline, 1999;Schell et al, 2000) may be a result of these oceanographic changes and thus contribute, in part, to the observed lower values in the CAI/R whales relative to the EAI/R and GOA/R groups. Furthermore, although both the EAI/R and GOA/R whales are likely consuming salmon as a substantial part of their diets (Matkin and Saulitis, unpublished data;Saulitis et al, 2000), the CAI/R residents may also be consuming locally available prey (e.g., pollock, Pacific cod, Pacific halibut), because salmon may be less available in the Central Aleutians due to lack of anadromous streams and major migratory pathways. Thus, differences in stable isotope values noted among the regional groups of resident killer whales may be significantly influenced by differences in the signatures at the base of the food chain, as well as by differences in prey specialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower d 15 N values at the base of the food chain in the Central Aleutian islands (Kline, 1999;Schell et al, 2000) may be a result of these oceanographic changes and thus contribute, in part, to the observed lower values in the CAI/R whales relative to the EAI/R and GOA/R groups. Furthermore, although both the EAI/R and GOA/R whales are likely consuming salmon as a substantial part of their diets (Matkin and Saulitis, unpublished data;Saulitis et al, 2000), the CAI/R residents may also be consuming locally available prey (e.g., pollock, Pacific cod, Pacific halibut), because salmon may be less available in the Central Aleutians due to lack of anadromous streams and major migratory pathways. Thus, differences in stable isotope values noted among the regional groups of resident killer whales may be significantly influenced by differences in the signatures at the base of the food chain, as well as by differences in prey specialization.…”
Section: Discussionmentioning
confidence: 99%
“…Transients are thought to prey solely on marine mammals and residents are believed to principally consume marine fish, in particular salmon. Thus, transient killer whales are members of a ''mammal-eating'' ecotype, whereas residents belong to a ''fish-eating'' ecotype (Baird and Dill, 1995;Ford et al, 1998;Saulitis et al, 2000). A third group, the ''offshores,'' has also been proposed (Ford et al, 2000) to describe whales most commonly encountered in outer coastal waters between California and Alaska (Dahlheim, unpublished data;Ellis, 2005;Krahn et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Two sympatric populations in the Pacific Northwest have partitioned their niche according to a diet consisting exclusively of salmon or marine mammals (Ford et al, 1998;Saulitis et al, 2000). Another example of social transmission of foraging behavior concerns Guinet & Bouvier's (1995) report of adult killer whales in the Crozet Archipelago teaching their calves how to beach themselves and capture pinniped prey.…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 99%
“…However, several studies have identified highly specialized populations that consume a narrow range of prey [25,26]. For example, in the near shore waters of the Northeast Pacific, there are two sympatric ecotypes of killer whales, which are thought to have non-overlapping prey preferences: one ecotype feeds on fish, whereas the other feeds upon mammals [25,26]. These North Pacific ecotypes are reproductively isolated, as indicated by strong lineage sorting of mitochondrial DNA (mtDNA) and strongly bimodal genotypic clustering.…”
Section: Study Systemmentioning
confidence: 99%
“…The foraging strategies of mammaleating killer whales are adapted to hunting large, single prey items with acute hearing, and they therefore typically travel in small groups, with a mean group size of three to five animals and forage in silence [24,26,[56][57][58][59][60]. By contrast, rspb.royalsocietypublishing.org Proc R Soc B 280: 20131481 the foraging strategies of fish-eating killer whales are adapted to hunting smaller, clustered prey with poor hearing, and therefore form a wide range of group sizes [24,26,60] and typically vocalize at a higher rate than mammal-eating killer whales [56][57][58][59]. However, the plastic nature of these phenotypic traits associated with each foraging strategy allows switching between strategies [61].…”
Section: (D) Generalism Trade-offs and Niche Variationmentioning
confidence: 99%